Transformational Leadership of Kindergarten School Principal Based on â€œIntegrity, Professionality, and Entrepreneurshipâ€ - Setiyaningtiyas, Nerita; Hartutik, Hartutik (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2022)
The study aims to develop the concepts of school culture through the transformational leadership process. The study used qualitative methods with a phenomenological design involving case studies in Citra Berkat Kindergarten Surabaya. To collect the data, the researchers used interviews, observation, and documentation. Data analysis employed qualitative and descriptive techniques. The results of this study showed that Citra Berkat Kindergarten Surabaya has developed school cultur based on values. It was concluded that IPE (Integrity, Professionality, and Entrepreneurship) for kids is relevant to introducing entrepreneurship in early childhood education. The transformational leadership of the principal school of Citra Berkat Kindergarten has a complete picture of how the organization should be. The school principal expresses the organizational values basic principles to be shared and realized by all components of Citra Berkat Kindergarten.